Highly efficient thermal oxidation and cross-linking reaction of catechol functionalized polyacrylonitrile copolymer composites for halogen-free flame retardant. (1st March 2020) - Nam, Ki-Ho; Jin, Jeong-Un; Lee, Jae Hyeok; Kim, Jongho; Chung, Yong Sik; Yeo, Hyeonuk; You, Nam-Ho; Ku, Bon-Cheol
Abstract: There have been major efforts to make polyacrylonitrile (PAN) flame retardant using halogens, heavy metals, transition metals, and phosphorus-organic compounds. These retardants may reduce the risk of fire, but they also involve high cost, toxicity, and related ecological issues. In an effort to mitigate some of these negative factors, we herein report the development of a green flame-retardant PAN based on bio-inspired dopamine methacrylamide (DMA) co-monomer. This polymer was synthesized through free radical polymerization of AN and acetonide-protected dopamine methacrylamide (ADMA), followed by deprotection of ADMA. Systematic investigation of the structural evolution of P(AN- co -DMA) confirmed that DMA provides a kinetic advantage for initiating the cyclization of PAN at significantly lower temperatures (209 °C) as well as for controlling effectively the amount of heat generated. Moreover, the effective radical scavenging capability of DMA, and the formation of a carbonaceous layer on the polymer surface, greatly improved the flame-retardant performance of PAN, without the use of conventional additives. This resulted in low heat-release capacity (HRC) and high limiting oxygen index (LOI) values of 58 Jg –1 K −1 and 37% (superior to those values of Nomex®), respectively. The thermal oxidative stabilization (TOS) process and flame retarding properties of PAN/GO composites were further investigated. TOS process and flame retarding mechanism were found to be influenced by ionic interaction and hydrogen bonding between polymer and nanomaterial. This work opens up a facile and sustainable methodology for the design of environmentally friendly and high-performance flame retardants and composites. Graphical abstract: Image 1 Highlights: The bio-inspired DMA co-monomer and polymers, P(AN- co -DMA) were newly synthesized. Catechol unit of P(AN- co -DMA) provides a kinetic advantage for TOS process and high flame retarding properties. P(AN- co -DMA) showed ultra-low heat release capacity (58 Jg –1 K –1 ) and high limiting oxygen index (37%).